Immunoglobulin G (IgG) and IgG Subclass Concentrations Differ According to Sex and Race - Harkness, Tyler (Ann Allergy Asthma Immunol, 2020)
BACKGROUND: Serum immunoglobulin G (IgG) concentrations are integral to the workup of immune deficiencies and IgG4-related disease (IgG4-RD). Demographic differences in IgG concentrations are poorly described but could influence test interpretation, contribute to racial disparities in primary immunodeficiency diagnosis, and explain demographic differences in IgG concentrations in IgG4-RD. OBJECTIVE: To assess differences in IgG and IgG subclass concentrations according to sex and race. METHODS: We identified patients with IgG and IgG subclass concentrations measured in a large healthcare system. Multivariate-adjusted differences in IgG and IgG subclass concentrations and the proportion of subjects with results outside of reference ranges according to sex and race were estimated. RESULTS: Of the 12,851 patients, the mean age was 54.7 years and 7,917 (62%) were female. 11,673 (91%), 611 (5%), and 302 (2%) were White, Black, and Asian, respectively. Compared to White patients, Asian and Black patients had higher mean concentrations of IgG (1340.0 and 1504.4 vs. 988.1 mg/dL; p<0.001), IgG1 (782.0 and 938.4 vs. 592.4 mg/dL, p<0.001), IgG2 (493.5 and 384.2 vs. 305 mg/dL; p<0.001), IgG3 (76.6 and 91.9 vs. 55.9 mg/dL; p<0.001), and IgG4 (140.4 and 53.6 vs. 41.6 mg/dL; p<0.001). IgG4 concentrations were higher in males than females (56.3 vs. 37.4 mg/dL; p < 0.001). Similar observations were made when comparing the proportions of patients with results outside of reference ranges and after stratifying by diagnosis. CONCLUSION: IgG and IgG subclass concentrations differ according to sex and race. These findings may have implications for the interpretation of these test results but require confirmation in diverse, healthy populations.